Development and characterization of spray-dried soy sauce-calamansi mix. - Amancio, Jullie Anne Bolivar (2018.)
Soy sauce mixed with calamansi is a famous condiment in the Philippines. It is also used as a dipping sauce or marinade. This study was conducted to produce a soy-sauce calamansi powder by spray drying. Five different ratios with varying amounts of calamansi juice in a fixed volume of soy sauce were prepared and subjected to rank preference test. The ration with 60% calamansi juice in soy sauce was declared as the most preferred ratio. This ration was followed in the production of soy-sauce calamansi powder using the spray drying process. Spray drying resulted to a process yield of 54.10 ± 0.06%. The resulting powder had a pH value of 2.82 ±0.01, titratable acidity of 2.98 ±0.08% citric acid, total soluble solids of 18.23 ±0.1 °Brix, and a bulk density of 0.667 ±0.0001g/ml. The moisture content (dry basis) of the powdered product was 1.75 ± 0.05% and thge water activity value was 0.26 ± 0.01. The estimated yeasts and molds count of the powder was 20 cfu/g. The powdered product was described as having brown to dark brown color, moderately strong to strong soy sauce aroma, slightly perceptible to moderately strong calamansi aroma, and moderately smooth to smooth texture (handfeel). The soy sauce-calamansi powder was reconstituted with varying ratio of water and powder. kramer's Rank Sum Test at 5% level of significance showed that Ratio C (1:9 powder to water) was the most preferred ratio for the reconstitution. The reconstituted product had pH value of 2.74 ± 0.02 and titratable acidity of 3.97 ± 0.1% citric acid. The reconstituted mixture was described as having brown to dark brown color, moderately strong to strong soy sauce aroma, slightly perceptible to moderately strong calamansi aroma, moderately strong to strong soy sauce flavor, and slightly perceptible to moderately strong calamansi flavor. General acceptability of the product showed that 41.67% rated the product as like much. None of the consumer respondents disliked the products.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Soy sauce-calamansi powder; Soy sauce -- Condiment; Condiments